2017
DOI: 10.4172/2155-6113.1000703
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Nutritional Status and Associated Factors among Prisoners Living with HIV/AIDS in Kality Prison, Addis Ababa, Ethiopia

Abstract: Introduction: In the case Human Immune Deficiency virus/Acquired Immune Deficiency Syndrome (HIV/AIDS), prison conditions not only contribute to the risk of transmission, it also hastens the progression of HIV and deterioration in the health of prisoners living with HIV/AIDS. Prisons typically comprise marginalized sections of society and at high nutritional risk due to lack of diet diversity, as these prisoners depend on few kinds of food for a long time and in a situation, adequacy of nutritional requirement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 1 publication
1
7
2
Order By: Relevance
“…The finding from this study revealed that 18.6% (95%CI: 14.4%, 22.8%) of the respondents were undernourished. This prevalence was lower than the findings obtained from studies in Kality (43%) [ 14 ] and Tigray region prisons (25.2%) [ 2 ]. This discrepancy may be due to the difference in the study participants; the study participants in Kality and Tigray region had additional co-morbidities.…”
Section: Discussioncontrasting
confidence: 75%
See 4 more Smart Citations
“…The finding from this study revealed that 18.6% (95%CI: 14.4%, 22.8%) of the respondents were undernourished. This prevalence was lower than the findings obtained from studies in Kality (43%) [ 14 ] and Tigray region prisons (25.2%) [ 2 ]. This discrepancy may be due to the difference in the study participants; the study participants in Kality and Tigray region had additional co-morbidities.…”
Section: Discussioncontrasting
confidence: 75%
“…i.e. they were HIV infected and had upper respiratory tract infection respectively [ 2 , 14 ]. However, the prevalence was higher than the findings of the studies conducted in Iran (14.2%) and Côte d’Ivoire (14.06%) [ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations